1982
DOI: 10.2307/3544690
|View full text |Cite
|
Sign up to set email alerts
|

Microfungi in Ecosystems: Fungal Occurrence and Activity in Litter and Soil

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(64 citation statements)
references
References 88 publications
7
53
0
2
Order By: Relevance
“…Osono and Takeda (2002) and Urairuj et al (2003) noted that Xylaria species were exceptional among microfungal leaf decomposers in having ligninolytic enzymes. On the other hand, Flanagan (1981), Kjøller and Struwe (1980, 1982, Wainwright (1988), Sin et al (2002) and Bucher et al (2004) found that most fungi were versatile in their carbon utilization, which is consistent with the hypothesis of Hooper et al (2000). Nevertheless, diversity of carbon substrates would still be expected to increase decomposer diversity given intermediate levels of substrate selectivity among the decomposers (Hooper et al, 2000).…”
Section: Article In Presssupporting
confidence: 66%
See 1 more Smart Citation
“…Osono and Takeda (2002) and Urairuj et al (2003) noted that Xylaria species were exceptional among microfungal leaf decomposers in having ligninolytic enzymes. On the other hand, Flanagan (1981), Kjøller and Struwe (1980, 1982, Wainwright (1988), Sin et al (2002) and Bucher et al (2004) found that most fungi were versatile in their carbon utilization, which is consistent with the hypothesis of Hooper et al (2000). Nevertheless, diversity of carbon substrates would still be expected to increase decomposer diversity given intermediate levels of substrate selectivity among the decomposers (Hooper et al, 2000).…”
Section: Article In Presssupporting
confidence: 66%
“…Fallen leaves from different plant species can differ greatly in their contents of lignin, cellulose, secondary plant compounds and other components; some may be inhibitory to fungal growth while each requires a diverse array of microbial enzymes for their degradation (Parkinson, 1981;Kjøller and Struwe, 1982;Heal and Dighton, 1986;Wainwright, 1988;Cromack and Caldwell, 1992;Cox et al, 2001). Such differences in leaf components may contribute to differences in microfungal species composition and frequencies (Bills and Polishook, 1994a;Polishook et al, 1996;Wong and Hyde, 2001;Zhou and Hyde, 2001) that have been documented among plant species and communities (Swift, 1976;Christiansen, 1981Christiansen, , 1989Cook and Rayner, 1984), including both temperate (Christensen, 1969) and tropical forests (Cowley, 1970;Cornejo et al, 1994;Polishook et al, 1996;Lodge, 1997).…”
Section: Article In Pressmentioning
confidence: 99%
“…Fungi are considered to be the key players in litter decomposition because of their ability to produce a wide range of extracellular enzymes, which allows them to efficiently attack the recalcitrant lignocellulose matrix that other organisms are unable to decompose (Kjoller and Struwe, 1982;de Boer et al, 2005). Biochemical decomposition of leaf litter is a sequential process that initially involves the loss of the less recalcitrant components (for example, oligosaccharides, organic acids, hemicellulose and cellulose) followed by the degradation of the remaining highly recalcitrant compounds (for example, lignin or suberin).…”
Section: Introductionmentioning
confidence: 99%
“…For example, litter is thought to be initially colonized by "sugar fungi" (sensu Garrett, 1963) which have neither cellulolytic or ligninolytic ability. These species are replaced over time by cellulolytic fungi, and finally the litter is colonized by ligninolytic fungi (12); however, the general validity of this scheme has been questioned (11,20,29,43). Moreover, testing this hypothesis has been difficult, because determining the function of fungal species typically requires isolating organisms and examining their effects on defined substrates in pure culture (7,15,(30)(31)(32), which has well-documented limitations (2).…”
mentioning
confidence: 99%